PRAKTIK PENGOBATAN TRADISIONAL TERHADAP PENANGANAN DIARE BALITA PADA MASYARAKAT SUKU BAJO - Muhammad Ridha Afdhal; Dicky Indirwan (Illea : Journal of Health Sciences, Public Health and Medicine, 2026)
The background of this research is based on the high incidence of childhood diarrhea in coastal communities, which is often exacerbated by delays in medical treatment due to strong socio-cultural factors. The purpose of this study was to analyze the influence of traditional medical practices of the Bajo Tribe on the management of toddler diarrhea and to design a culture-based health promotion strategy. The object of this study was the Bajo Tribe community in Bajoe Village, Bone Regency, focusing on mothers of toddlers, traditional healers, and community leaders. The research method used a qualitative case study approach through the analysis of personalistic belief models, social norms, and evidence-based health effectiveness. The results showed that jappi-jappi (incantations) became the main choice that was unsafe as a sole treatment because it delayed medical rehydration, while the use of cangi-cangi leaves (guava leaves) was relatively safe as a complementary therapy due to its antibacterial properties. The conclusion of the study confirms that cultural constraints and collective decision-making trigger delays in medical referrals, leading to the design of the "Sipulung Sehat" program as a health promotion intervention that integrates local culture and empowers traditional healers as referral partners.